Efficacy and safety of topical 2% dorzolamide and 0.5% timolol in cases of open angle glaucoma in a tertiary care hospital of East Singhbhum: an observational, prospective and comparative study - Chandra, Akash; Kumar, Manish; Mishra, Amrendra Narayan (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Present study was undertaken to evaluate and compare the efficacy and side effects of 2% dorzolamide and 0.5% timolol in patients with open angle glaucoma. Methods: There were 60 randomly selected patients were equally divided into Group I (n=30) and Group II (n=30). Further both groups were divided into IA (n=10), IB (n=20), IIA (n=10) and IIB (n=20). 2% Dorzolamide hydrochloride in Group IA and IIA and 0.5% Timolol maleate in Group IB and IIB was administered for 24 weeks. Patients were evaluated for general and ocular examinations on day of enrolment and then at the end of 1st, 4th, 8th and 24th week. Adverse effects of the drug during study period were also noted. Mean±SD, t value, p value and comparison between groups were analysed by graph pad software. Results: At the end of 24 weeks difference in mean reduction of IOP was not significant with 6.2±1.85mm Hg (Right eye) and 5.55±1.68mm Hg (left eye) and 4.72±2.97mm Hg (Right eye) and 5.37±1.24mm Hg (left eye) in Group IA and Group IIA respectively. At the end of 24 weeks difference in mean reduction of IOP was not significant with 5.06±1.62mm Hg (Right eye) and 4.40±1.96mm Hg (left eye) and 4.30±1.41mm Hg (Right eye) and 4.12±2.08mm Hg (left eye) in Group IB and Group IIB respectively. Fall in both systolic and diastolic blood pressure in both the groups were significant. Both drug regimens were well-tolerated, and no serious drug-related adverse effects were reported. Conclusions: Dorzolamide was more efficacious for reduction of intra ocular pressure, well-tolerated, had low allergic response and had a favourable ocular, cardiovascular and respiratory safety profile than Timolol.